Early Buddhism as philosophy of existence freedom and death - Babbitt, Susan E. 1953- (Anthem Press, 2022)
Philosophical liberalism is the dominant view in the world today. Even those who reject liberalism philosophically, subscribe to its view of freedom, which is a negative view, common to liberalism, libertarianism, and anarchism. The alternative is recognition of nature, thoroughly, applied fully to human beings. The Buddha set it out as a philosophy, and he lived it. It was a practice. It brings death back into life. The common view is that death is the opposite of life. Yet death is part of life, from the beginning. We see this in many great writers, Dostoevsky, for example. His characters find human communion in suffering, despite their differences. Contradictions are inherent in life, but we find our way, not a single way. It brings realism back, which is truth. It has been present in human societies throughout history. It has been banished because of a false view of truth, connected to a false view of freedom. It could be recognized as philosophy. The Buddha taught people simply. There was no dogma. He did not teach them to follow him but to be masters of their own salvation. Unless this view is recognized as Philosophy, as it should be, including truth, it will again become religion, rather than a way of life, an art of living